An Improved Single Stage Transformer-Less Multilevel Inverter Under Conventional And Advanced MPPT Algorithms for Photovoltaic Application (Journal of University of Babylon for Engineering Sciences, 2023)
A transformer-less single-stage, grid-connected PV system is increasingly introduced with a multilevel inverter (MLI). MLI is employed to integrate the PV system with the utility grid due to its high efficiency, low cost, smaller size and weight. However, The leakage current due to the absence of galvanic isolation is one of the drawbacks in such system. This paper investigates a single phase three level Neutral point clamped (NPC) inverter to be employed in a single stage grid connected PV system. The system is characterized with a unity power-factor and low current total harmonic distortion (THD), low voltage stress on the semiconductor switches, no shoot through problems, high reliability and efficiency. The paper proposes the improved split-inductor (ISI-NPC) inverter as an effective candidate to be employed in such transformer-less PV system.  Hysteresis current control (HCC) is designed to track the inverter output current and force it to be zero in order to achieve high power quality grid power and maintain unity power factor. A conventional and advanced maximum power point tracking algorithms including perturb and observe (P&O) and artificial neural-network (ANN) are examined to ensure extracting the maximum power from the PV panel. The whole system is designed and tested in this work. A better performance is achieved under ANN approach with HCC. The results validate the ability of the ISI-NPC inverter under HCC control and artificial neural network to transfer PV maximum power to the grid with a unity power factor, high power quality, very low current THD with a 0.37% less semiconductor switches stress, and thus high reliability. Therefore, the paper highlights that ISI-NPC is considered as an effective MLI to be employed in such system.